#### Answer

(a) -13
(b) -5

#### Work Step by Step

We are given:
$f(x)=2x-3$ and $g(x)=4-x^2$
We evaluate:
(a) $(f\circ f)(-1)=f(f(-1))=f(2(-1)-3)=f(-2-3)=f(-5)=2(-5)-3=-13$
(b) $(g\circ g)(-1)=g(g(-1))=g(4-(-1)^{2})=g(4-1)=g(3)=4-3^{2}=4-9=-5$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(a) -13
(b) -5

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.